2004
DOI: 10.1111/j.1751-908x.2004.tb01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recoveries by Lead Fire Assay and Nickel Sulfide Fire Assay in the Determination of Gold/ Platinum/ Palladium and Rhenium in Sulfide Ore Samples

Abstract: We compared the recovery of gold, palladium and platinum by two fire assaying procedures, using nickel sulfide and lead as collectors. The presence of appreciable amounts of sulfide minerals in the sample caused interferences in both procedures. An in‐house reference sample, a reference sample of high‐grade sulfide ore and samples of high sulfide content from the Recsk porphyry copper ore in Hungary were analysed by both methods. The elements were determined by inductively coupled plasma‐atomic emission (ICP‐A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…This, coupled with past results, suggests that the presence of a high sulfur concentration in the sample increases the total Re recovery, but that it always remains incomplete. Juvonen et al (2004) also found that adding extra sulfur will increase Re recovery. However, the authors do not recommend this technique to separate Re before determination.…”
Section: Rhenium Determinationmentioning
confidence: 93%
“…This, coupled with past results, suggests that the presence of a high sulfur concentration in the sample increases the total Re recovery, but that it always remains incomplete. Juvonen et al (2004) also found that adding extra sulfur will increase Re recovery. However, the authors do not recommend this technique to separate Re before determination.…”
Section: Rhenium Determinationmentioning
confidence: 93%
“…NiS-FA can be used to collect both PGEs and gold, but its efficiency for gold determination has been very low. Juvonen et al [40] compared NiS-FA with Pb-FA in terms of their collection efficiencies of Au, Pt, Pd, and Rh and found that the gold recovery of NiS-FA was twice as low as that of Pb-FA at low gold concentrations. Plessen and Erzinger [41] reported that the gold recovery did not exceed 70% when NiS-FA was used to analyze rocks.…”
Section: Dry Digestion Methodsmentioning
confidence: 99%
“…Literatürde yayınlanan son çalışmalarda PGM'lerin çeşitli endüstriyel proseslerden elde edilen matlarda zenginleştirilmesi ve bu matların çözümlendirilme şartlarının belirlenmesi üzerine araştırmalar yapılmıştır. Örneğin; Ni-Cu-Fe-S Peirce Smith konvertör matı; Ni-Cu konvertör matı; Ausmelt yöntemi konvertör matlarının çeşitli şartlarda farklı çözücüler varlığında çözümlendirilmesi incelenmiş ve PGM'lerin geri kazanımı üzerine bir dizi çalışmalar yürütülmüştür [24][25][26]. Fakat bu çalışmalar genellikle sülfürlü cevherlerde var olan PGM'lerin geri kazanımı üzerine gerçekleştirilmiştir.…”
Section: Introductionunclassified
“…bulunan platin grubu metallerin çeşitli spektroskopik yöntemle analizleri hakkındadır. Bu çalışmalarda genellikle spektroskopik teknikler karşılaştırılmış ve karşılaşılan sorunlar için alınması gereken önlemler araştırılmıştır [23,24]. NiS matı yönteminin katalitik dönüştürücüler kullanılarak reaksiyon şartlarının belirlenmesine yönelik gerçekleştirilen çalışmada %99'a yakın PGM geri kazanım elde edilmiş fakat PGM'lerin çözeltiye alındıktan sonra selektif olarak çöktürülmesi, daha sonra çözeltideki nikelin tekrardan kazanılarak yöntemde kullanımı hakkında çalışmalar eksik kalmıştır [4].…”
Section: Introductionunclassified